Analisa Pengelolaan Sampah Pada TPS Rumah PKD Tlogomas, Kecamatan Lowokwaru, Kota Malang, Jawa Timur - Ndona, Fransiskus Saverius; Yurnalisdel, Yurnalisdel; Sulistyani , Kiki Farida (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
The growth of historical communities, the increase in population every year, and the increase in household and industrial waste generated by the community, which further adds to the burden on the soil, air, and rivers that flow through residential neighborhoods. Waste management at TPS Rumah PKD Tlogomas aims to serve the population for the domestic household waste they produce, indirectly maintaining public health and creating a good, clean and healthy environment. The existence of waste in the TPS Rumah PKD Tlogomas often causes problems for the environment, such as: Decomposing garbage produces gases that smell bad and are harmful to health, garbage that is scattered out of place, lack of public awareness about the waste disposal and management system, and lack of waste transportation equipment which results in accumulation of garbage. The objectives of this study are: (1) To determine the characteristics of waste in the form of organic and inorganic waste; (2) To determine the volume of waste in TPS Rumah PKD Tlogomas; and (3) To determine the development of waste management infrastructure. The method used is the literature method and observation study approach with variables including location, boundaries, TPS area and facilities and infrastructure. The results of data analysis show that TPS Rumah PKD Tlogomas produces 0.693 kg of waste per person every day, consisting of organic and inorganic waste, from a total of 20,215 people. Based on survey data, TPS Rumah PKD Tlogomas has 24 drums, but the calculation results show that there will be an overcapacity of 28 drums in 2026. To prevent overcapacity, TPS Rumah PKD Tlogomas requires an additional 4 drums in 2026.